Fun home : a family tragicomic - Bechdel, Alison (Jonathan Cape, 2006)
DISCOVER the BESTSELLING GRAPHIC MEMOIR behind the SENSATIONAL LONDON MUSICAL The award-winning musical adaptation that took America by storm now playing to five star reviews at the Young Vic | `A sapphic graphic treat' The TimesA moving and darkly humorous family tale, pitch-perfectly illustrated with Alison Bechdel's gothic drawings.